SimObturation: Virtual Reality Application for Simulation of Dental Obturation Procedure Training with Phantom Omni Device Integration - Virgulino, Tamirys; Oliveira, Jauvane (Anais do Simpósio de Realidade Virtual e Aumentada (SVR), 2019)
The constant evolution of virtual reality applications in areas of dentistry has been gaining proeminence and contributing in several areas of knowledge associated with the training of professionals to perform the dental procedures. In this work, we present the modeling of a virtual simulator prototype for training an obturation process, using the Phantom device a represent of the clinical instrument with interaction with the tooth represent by an OBJ file, allowing interaction of the professional in surgical procedure. In addition, the device simulates the generation of strength, tactile sensation, kinesthetic and proprioceptive sensation through its indicator when collision occurs with the object. The prototype is under development, preliminary testing will be supported by experts in the field, who will validate the visual and tactile feedback of the prototype.